Determination of engine oil change interval for patrol engines based on actual operating time - A. A. Abakarov; Sh. M. Igitov; Ali A. Abakarov (Вестник СибАДИ)
Introduction. This paper shows the results of a study of the frequency of maintenance of passenger cars in various operating conditions, and provides recommendations for replacing the engine oil of gasoline engines (category SN classification according to API) according to the actual engine operating time (moto-hours). The service book of passenger cars contains the regulations for car maintenance with a list of operations that must be performed. The oil change intervals specified in the Regulations on Maintenance and Repair of Rolling Stock of motor Transport and the factory instructions do not take into account the specifics of the operation of vehicles. Depending on the road and climatic conditions and the operating mode, the standard maintenance schedule can be adjusted, in particular, the frequency of engine oil changes. The scientific novelty of the work is to determine the intervals of car maintenance for specific operating conditions.Materials and methods. The paper presents an analysis of Russian and foreign car maintenance systems, in particular, the oil change intervals of gasoline engines in European countries, the United States and Japan.The results of operational and resource tests of motor oils of gasoline engines carried out by methods of measuring their physical and chemical properties are presented.Results. In this paper, based on the analysis of the problem, recommendations for changing oil in gasoline engines by motorcycle hours for the conditions of the Republic of Dagestan (RD) are developed.The use of external and built-in technical means for calculating the motor hours allows you to determine the recommended oil change interval.Discussion and conclusion. In this paper, on the basis of research on a certain number of vehicles operating in various (including difficult) conditions, recommendations are developed that allow you to determine the rules of car maintenance for various operating conditions.